Réponses

  • Utilisateur Brainly
2014-03-16T14:21:04+01:00
Factoriser : 
A ) 3(4x +3)+( 4x+3)(7-2x)
=(4x+3)(3+7-2x)
=(4x+3)(-2x+10)

B ) ( x+3)(5x-2)+10(x+3)-(5x-1)(x+3)

=(x+3)(5x-2+10-5x+1)
=(x+3)(9)
Meilleure réponse !
  • Utilisateur Brainly
2014-03-16T14:24:01+01:00
Factorisation:

A)
3 (4x+3) + (4x+3) (7-2x) ⇒ On remarque le facteur commun
(4x+3) (3 + (7-2x) ) ⇒ On factorise par (4x+3)
(4x+3) (3+7-2x)
(4x+3) (-2x+10)

B)
(x+3) (5x-2) + 10 (x+3) - (5x-1) (x+3)  ⇒ Facteur commun
(x+3) (5x-2 +10 - (5x-1) ) ⇒ On factorise par (x+3)
(x+3) (5x +8 -5x +1)
9(x+3)

Voilà ! J'espère t'avoir aidé(e) ! :)